P224 Efficacy and long-term safety of QMF149 (indacaterol acetate/mometasone furoate) versus mometasone furoate and versus salmeterol xinafoate/fluticasone propionate in patients with inadequately-controlled asthma: The PALLADIUM study. (12th November 2019) - van Zyl-Smit, R; Krull, M; Gessner, C; Gon, Y; Richard, A; de los Reyes, A; Shu, X; Pethe, A; D'Andrea, P
Abstract : Rationale: Long-Acting Beta2-Agonist/Inhaled Corticosteroids (LABA/ICS) Fixed-Dose Combinations (FDCs) have been found to be safe and effective in asthma management; however, most of the available therapies require twice-daily(b.i.d.) dosing to achieve an optimum therapeutic effect. QMF149 is a once-daily(o.d.) FDC of indacaterol acetate(LABA) and mometasone furoate(MF, an ICS) delivered by the Breezhaler ® device. This Phase-III study(NCT02554786 ; The PALLADIUM Study) is part of the PLATINUM clinical program which supports the development of both QMF149 and QVM149 (indacaterol acetate, glycopyrronium bromide and mometasone furoate). Specifically, the PALLADIUM study evaluates the efficacy and safety of once-daily QMF149 150/160μg and 150/320μg(via Breezhaler ® ) versus ICS alone: MF 400μg o.d. and 800μg(400μg b.i.d.[via Twisthaler ® ]) or salmeterol xinafoate/fluticasone propionate(SFC) 50/500μg b.i.d.(via Accuhaler ® ) in inadequately-controlled asthmatics. Methods: The PALLADIUM study is conducted in patients (age:≥12 to ≤75 years) with pre-bronchodilator FEV1 % predicted:≥50% to <85%, who are symptomatic at screening (ACQ-7 score≥1.5) despite treatment with medium/high stable ICS and/or LABA/ICS low-dose combination, and qualify for medium/high-dose LABA/ICS combination. Patients are randomized to receive QMF149 or MF or SFC for 52 weeks (Figure ). At week 26, trough FEV1 (primary endpoint) and asthma control by ACQ-7 score (key secondary endpoint) are to be evaluated in QMF149 versus MF. During 52 weeks, treatment effect on exacerbations in terms of time-to-first exacerbation and rate of exacerbations are to be assessed in all patients. Additional secondary endpoints include the comparison of QMF149 150/320μg versus SFC 50/500μg in terms of trough FEV1, ACQ-7, PEF and rescue medication use at Week 26 and 52. Safety is also assessed. Results: Of 2216 patients randomized, all have completed the study (52 weeks treatment or premature withdrawal) at the time of abstract submission. Database lock is scheduled for August 2019. The final study results, expected in September 2019, will be included in the final abstract and presentation. Conclusion: This 52-week study is the first to evaluate the efficacy and long-term safety of once-daily QMF149 at different doses(150/160μg and 150/320μg) versus MF(400μg o.d. and 400μg b.i.d.) and versus currently available LABA/ICS standard-of-care SFC 50/500μg b.i.d. in inadequately-controlled asthmatics, in terms of exacerbation reduction, lung function, asthma control and rescue medication use.